Formulation and Evaluation of Physical Properties of Antioxidant Effervescent Granules and Extract of Karamunting Flower (Melastoma malabathricum L.) - Shesanthi Citrariana; Yahya Febrianto; Thathit Suprayogi; Emma Ayudia Noriadita (LPPM Institut Studi Islam Sunan Doe, 2024)
Karamunting (Melastoma malabathricum L.) contains several compounds with pharmacological activities including antioxidant, analgesic, anti-inflammatory, antipyretic and diuretic. Karamunting flowers contain flavonoid compounds, saponins and tannins. Tannin compounds can stabilize free radicals by complementing the electron deficiency of free radicals. To increase the utilization of karamunting flowers, it is formulated in the form of effervescent granules. This study aims to determine the ethanol extract of karamunting flower (Melastoma malabathricum L.) with concentrations of 1%, 2%, and 3% can be formulated in the form of effervescent granules. The physical properties of the granules were tested which included organoleptic test, flow rate test, granule compressibility test, dissolving time test and pH of effervescent granules. The results showed that formula 3 with a concentration ratio of 3% ethanol extract was a formula that met the requirements for the physical properties of the granules, namely with a sweet and sour taste, a characteristic odor of karamunting, and a dark purple-brown color. With an average flow rate of 2.853 g/sec, average compressibility of 21.12%, an average dissolving time of 7.52 seconds and a pH measurement of 5.